Revenue diversification strategies in Ethiopian higher education system: A brief reflection - Kibrom Mengistu Feleke (Bahir Dar Journal of Education)
A university generally requires adequate financial resources for the success of its overall operations. Nevertheless, universities throughout the world, especially in developing ones, are struggling to obtain the necessary funds in order to satisfy the evergrowing demand of higher education. With the current massive higher education expansion in Ethiopia and the limited government capacity to adequately fund this expanding system, therefore, there is an urgent need for the public universities to work towards financial viability by broadening and diversifying their funding base. In an effort to establish financially sustainable ground, public universities need to generate revenues from non-governmental sources. With this in mind, this reflection discusses university financing trends and the subsequent financial austerity in Ethiopia. The paper also attempts to reflect on the strategies currently used by the public universities in diversifying their funding base in the face of increased financial demand for the rapidly expanding system of higher education in the country. The paper finally reflects on the implication of revenue diversification.